Inspirational Intuition – A new Managerial Approach to Operationalize a Success Factor for Inventions - Jochem Müller (ZBW - Leibniz Information Centre for Economics, 2021)
Intuitive competence is an important human characteristic. This article discusses the importance of human intuition in the context of creating new knowledge. In particular, inspirational intuition plays an important role. In contrast, to Daniel Kahneman's fast, intuitive, and routine decision making in terms of a "System 1" (Kahneman 2011, pp. 19 ff.), inspirational intuition is shown to be a slow, incubational, and illuminative force. As a new "System 3", it forms an important core human capability to enable unprecedented knowledge with the help of original intuitions. The scientific paper shows the development of a helpful questionnaire to quantify inspirational intuition. This managerial approach captures individual differences in the potential of inspirational knowledge imagination and helps the management better realize and operationalize this intuitive competence in the competition of best ideas. – – Intuitive Kompetenz ist eine wichtige menschliche Eigenschaft. Dieser Artikel erörtert die Bedeutung der menschlichen Intuition im Zusammenhang mit der Schaffung neuen Wissens. Unter spielt insbesondere die inspirierende Intuition eine wichtige Rolle. Im Gegensatz zu Daniel Kahnemans schneller, intuitiver und routinierter Entscheidungsfindung im Sinne eines "Systems 1" (Kahneman 2011, S. 19 ff.), erweist sich die inspirierende Intuition als eine langsame, inkubatorische, und erhellende Kraft. Als neues "System 3" bildet sie eine wichtige menschliche Kernfähigkeit eine wichtige Kernfähigkeit des Menschen, um mit Hilfe origineller Intuitionen nie dagewesenes Wissen zu ermöglichen. Die wissenschaftliche Arbeit zeigt die Entwicklung eines hilfreichen Fragebogens zur Quantifizierung inspirierenden Intuition. Dieser betriebswirtschaftliche Ansatz erfasst individuelle Unterschiede im individuellen Unterschiede im Potenzial inspirierender Wissensvorstellungen und hilft dem Management Management, diese intuitive Kompetenz im Wettbewerb der besten Ideen besser zu erkennen und zu operationalisieren. Übersetzt mit www.DeepL.com/Translator (kostenlose Version)
Keywords: O; A1; 330; Intuition; Insprational; knowledge; imagination; inventory; creativity; competence; survey